1980
DOI: 10.1136/pgmj.56.662.833
|View full text |Cite
|
Sign up to set email alerts
|

Zinc metabolism in thyroid disease

Abstract: SummaryThis study was designed to evaluate the zinc metabolism in adults of both sexes with thyroid disease. Plasma and erythrocyte zinc concentration and urinary zinc excretion were investigated. The mean concentration of plasma zinc in hypothyroid patients and in euthyroid patients, previously either hyperthyroid or hypothyroid, was lower than that of control subjects, whereas no statistically significant differences were observed in plasma zinc values between hyperthyroid patients and control subjects. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 10 publications
3
14
1
Order By: Relevance
“…It has been reported that the serum or plasma levels of thyroid hormones were reduced by high Zn intake (Dean et al, 1991;Nishiyama et al, 1994) and were unchanged (Fujimoto et al, 1986) or increased (Oliver et al, 1987) on low Zn intake. In addition, the level of plasma zinc has been found to be correlated with plasma T 3 and T 4 levels (Nishi et al, 1980;Aihara et al, 1984). However, Morley et al (1981) found no correlation between serum zinc and T 4 level in alcoholic cirrhotic patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the serum or plasma levels of thyroid hormones were reduced by high Zn intake (Dean et al, 1991;Nishiyama et al, 1994) and were unchanged (Fujimoto et al, 1986) or increased (Oliver et al, 1987) on low Zn intake. In addition, the level of plasma zinc has been found to be correlated with plasma T 3 and T 4 levels (Nishi et al, 1980;Aihara et al, 1984). However, Morley et al (1981) found no correlation between serum zinc and T 4 level in alcoholic cirrhotic patients.…”
Section: Discussionmentioning
confidence: 99%
“…An interaction between thyroid hormones and zinc metabolism has been reported, and high serum zinc values have been noted in patients with hyperthyroidism (Nishi et al, 1980;Aihara et al, 1984). Furthermore, serum zinc content was found to be reduced in hypothyroid pigs (Schone et al, 1990).…”
mentioning
confidence: 97%
“…Serum Zn and Se were reported to be lower in patients with hypothyroidism or nodular goitre [18,39,40] compared to healthy control subjects, and Nishi et al [41] found no significant difference in serum Zn concentrations between patients with hypothyroidism and healthy subjects. In our study, serum Zn and Se concentrations did not change significantly after 12 weeks' supplementation.…”
Section: Journal Of the American College Of Nutritionmentioning
confidence: 99%
“…In pregnancy, erythrocyte car bonic anhydrase concentration rises with advancing ges tation, and this is attributed to the effect of progesterone [7], Since carbonic anhydrase is a zinc metalloenzyme, the erythrocyte carbonic anhydrase can be conveniently estimated by the measurement of erythrocyte zinc. Thy roid hormones depress the synthesis of carbonic anhydrase [3] and the RBC Zn concentration was found to be reduced in patients with thyrotoxicosis [1,2], but this change takes time to develop and is only apparent after the existing red blood cells are replaced by new ones formed after the onset of thyrotoxicosis.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc concentration in erythrocytes has been found to be reduced in patients with established thyrotoxicosis [1,2], Erythrocyte zinc reflects the activity of carbonic anhydrase, the synthesis of which inhibited by thyroxine [3], and therefore the effect of changes on thyroxine con centration is reflected only in developing but not circu lating red cells. Consequently, serial changes in erythro cyte zinc concentration tend to reflect the longstanding effect of thyroid hormones.…”
Section: Introductionmentioning
confidence: 99%